Advances in mergers and acquisitions. Vol. 5 - Finkelstein, Sydney; Cooper, Cary L. (Advances in mergers and acquisitions., 2006)
Each collection of articles that makes up a volume of Advances in Mergers and Acquisitions paints a picture of contemporary research on this topic. In this volume, we have seven contributions from scholars in North America, Europe, and Asia, and these papers collectively address acquisition strategy and acquisition integration, successful deals and unsuccessful ones, ownership structure and managerial structure, risk and return, knowledge preservation and knowledge transfer, building trust and cultivating emotions, and alliances and networks. This breadth of attention across the spectrum of research possibilities on mergers and acquisitions is remarkable in that it suggests both that this topic has morphed in recent years to encompass a broad array of issues that go far beyond what earlier generations of scholars concerned themselves with, and that there is still so much more to be learned about the processes and performance of mergers and acquisitions. One of the benefits of an edited volume of articles on a core topic is the opportunity it presents to bring together not only the diversity of topics described above, but a diversity of methods as well. The insights that emerge from these multiple methods may well be more varied than might otherwise be the case, and offer an additional potential contribution. In bringing together a set of seven different papers by scholars from different disciplines, with different research agendas, and hailing from different countries yet all of whom are tackling the same general phenomenon, this volume offers something that cannot be easily replicated in other forums. The diversity of disciplines, perspectives, and countries is remarkable, but so are the diversity of topics, issues, methodologies, and research questions they bring to bear to shed light on the same fundamental, and critical, feature of organizational life mergers and acquisitions. The book provides a diverse explanation of topics and methods, contains seven different papers provided by scholars from around the world, and is an excellent resource for researchers, students and practitioners.